(untitled) (Sciences & Technologie. C, Biotechnologies, 2015)
Two wood decay fungi have been isolated from the Pinus halepensis wood. They have been identified by their cultural and morphological aspects as: Tramates sp and Memnoniella sp. The isolation of the actinomycetes from different ecosystems has allowed us to obtain 80 pure strains. The agar disks technique has been employed to study the antifungal activity of these actinomycetes against the two fungi, which degrades the Pinus halepensis wood. Among all the isolated actinomycetes, 17 strains have presented an activity against at least one xylophage fungus tested. Among the 17 bacteria of actinomycetes, only one has shown a strong antifungal activity against the two fungal isolates. This actinomycete has been identified by the morphological and the chimio-taxonomical characters of the cellular wall as Streptomyces.